The negative effects of heavy metals in sandy soil and methods for reducing their damage "The soil of the Libyan Kufra Oasis as a model" - Zahia M. Bobaeda; Fathi A. Mohamed Elathrem (African Journal of Advanced Pure and Applied Sciences, 2024)
The current research seeks to identify the most important negative effects of heavy metals (organic/inorganic) that are saturated with the sandy soil in the Libyan Kufra Oasis, and to provide proposals and solutions to reduce their harm to the soil, humans, animals, and plants. The quantitative approach was relied upon in analyzing the study samples that were brought from three different areas of the Kufra Oasis, including typical agricultural production projects. After subjecting the samples to quantitative analysis through chemical analysis, we arrived at results including: Chemical analysis of samples from the three areas in the study resulted in the percentages of heavy metals in the sandy soil of the oasis as follows: mercury with a total average of (133.22) per million, and cadmium with a total average of (0.91) per million. Arsenic has a total average of (0.128) per million, chromium has a total average of (120.44) per million, thallium has a total average of (0.522) per million, lead has a total average of (60.11) per million, and molybdenum has a total average of (0.0041) per million. Nickel has a total average of (64.11) per million, copper has a total average of (3.45) per million, and zinc has a total average of (366.11) per million. It turned out that most of these rates are higher than the normal rate approved by the World Health Organization, which has serious effects on soil, plants, and human and animal health.